-(7z+10)=5z

Simple and best practice solution for -(7z+10)=5z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(7z+10)=5z equation:


Simplifying
-1(7z + 10) = 5z

Reorder the terms:
-1(10 + 7z) = 5z
(10 * -1 + 7z * -1) = 5z
(-10 + -7z) = 5z

Solving
-10 + -7z = 5z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-5z' to each side of the equation.
-10 + -7z + -5z = 5z + -5z

Combine like terms: -7z + -5z = -12z
-10 + -12z = 5z + -5z

Combine like terms: 5z + -5z = 0
-10 + -12z = 0

Add '10' to each side of the equation.
-10 + 10 + -12z = 0 + 10

Combine like terms: -10 + 10 = 0
0 + -12z = 0 + 10
-12z = 0 + 10

Combine like terms: 0 + 10 = 10
-12z = 10

Divide each side by '-12'.
z = -0.8333333333

Simplifying
z = -0.8333333333

See similar equations:

| 3y+2xy=10 | | 7=-7(3+m) | | 64k^4= | | (X+4)(5x+1)= | | x+1=x^2-25+25x | | 9x^2=4x-1 | | 4(w-15)-w=63+w | | x^2+5x-138=0 | | x+1=x^2-25-25x | | -49-6m=5+10(1-7m) | | 2x+18+3x-18=55 | | 4a-8=4-6a | | 17.3=3.2+x | | X+8=28-3x | | (5y+1)(2y-7)= | | -42=7-7x | | 5g+3=2g+9 | | 2(2x-70)=-(3x-35) | | -9x-45=-3x+87 | | 1=x(1-1.1) | | 3+x*4=-x*8 | | 4x^2+32x+1044=0 | | x^2+16x+10=7x-4 | | 32=x+x+5 | | 8j+4j=9j-6 | | 6x-108=126-7x | | x^2+x-2+x-2=x-9+x-9 | | 5=1+p | | (3-4a)(7-5a)= | | 2.25x+1.25t=13.50 | | 4(2)(g)+4(9)30=109 | | 5-2[6-(8y-2)]= |

Equations solver categories